1984
DOI: 10.1093/sleep/7.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Activity of the Basolateral Amygdala, Cingulate Gyrus, and Hippocampus During REM Sleep in the Cat

Abstract: Summary: We analyzed the electrical activity of the basolateral amygdala (BLA), anterior and posterior regions of the cingulate gyrus (A-CG and P-CG) , the dorsal hippocampus (DH) , the anterior ventral thalamic nucleus (AVTN), and the sensory motor cortex during the rapid eye movements and ponto-geniculo-occipital (PGO) activity of REM sleep in cats in chronic preparation. Polygraphic recordings and computational peri event averages using the phasic contractions of the lateral rectus muscle (LR) of the eyebal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 23 publications
2
22
1
Order By: Relevance
“…This view is consistent with recent observations regarding hallucinations in other contexts (Bentall, 1990;Woody & Szechtman, 1999). Moreover, the notion that hallucinations involve interactions between the amygdaloid complex and prefrontal cortical structures, such as the anterior cingulate, is consistent with recent work on REM dream imagery (Calvo & Fernández-Guardiola, 1984;Marquette et al, 1996), schizophrenia-related hallucinations (Cleghorn et al, 1992;Silbersweig et al, 1995), and hypnotically induced hallucinations (Szechtman, Woody, Bowers, & Nahmias, 1998). Szechtman et al, for example, found positive associations between regional cerebral blood flow (rCFB) in rostral portions within the right anterior cingulate and hallucinating subjects' ratings of externality and clarity of hallucinations.…”
Section: Discussionsupporting
confidence: 83%
“…This view is consistent with recent observations regarding hallucinations in other contexts (Bentall, 1990;Woody & Szechtman, 1999). Moreover, the notion that hallucinations involve interactions between the amygdaloid complex and prefrontal cortical structures, such as the anterior cingulate, is consistent with recent work on REM dream imagery (Calvo & Fernández-Guardiola, 1984;Marquette et al, 1996), schizophrenia-related hallucinations (Cleghorn et al, 1992;Silbersweig et al, 1995), and hypnotically induced hallucinations (Szechtman, Woody, Bowers, & Nahmias, 1998). Szechtman et al, for example, found positive associations between regional cerebral blood flow (rCFB) in rostral portions within the right anterior cingulate and hallucinating subjects' ratings of externality and clarity of hallucinations.…”
Section: Discussionsupporting
confidence: 83%
“…It is well known that there are anatomical and physiological correlations between the amygdala and the pons, where the PGO wave generator is located (Calvo and Fernandez-Guardiola 1984;Datta et al 1998) and that the time interval between PGO waves and REMs is on the order of tens of milliseconds in neurophysiological studies using animals (Datta and Hobson 1994). In contrast, the BOLD response of the PGO areas started several seconds before the occurrence of REMs in the present study.…”
Section: Activation Accompanying Remcontrasting
confidence: 49%
“…Because there are direct and/or indirect projections from the P wave generator in the pontine subcoeruleus region to many brain areas including the hippocampus and amygdala (Bland and Oddie 1998;Datta et al 1998Datta et al , 1999Hallanger and Wainer 1988;Usunoff et al 2006), the P wave generator in rats and the PGO wave generator in cats are believed to activate the hippocampus and amygdala (Calvo and Fernández-Guardiola 1984;Datta et al 2008). Recent findings showed that hippocampal and amygdala theta waves are induced by glutamatergic stimulation in the septum/hippocampus and amygdala, respectively (Bland et al 2007;Goutagny et al 2008;JafariSabet 2006;Sinfield and Collins 2006).…”
Section: Discussionmentioning
confidence: 99%